Promovendo conscientização : estratégias de educação para o trânsito voltadas para as crianças - Tomasi, Beatriz Magri (2024)
Introduction: Actions to prevent traffic incidents are significant topics in public management, requiring investments in multiple areas. Among these, it is essential to highlight infrastructure measures, effective enforcement of traffic laws, and, most importantly, educational actions. The challenge is that all these actions are complex and costly. Since the Federal Highway Police is part of the National Traffic System, it needs to enhance and invest in both enforcement and education for safer roads. Given the challenges that hinder the continuity and reach of educational actions with children, the main objective is to explore the specific work of traffic education carried out by the Federal Highway Police, in order to identify challenges and support the development of more effective practices for raising children's awareness about traffic. Theoretically, beyond traffic legislation itself, this research is supported by the fact that early childhood education plays a fundamental role in developing social, emotional, and cognitive skills, making it essential to target efforts toward this group. Another important point is traffic incident data, affecting thousands of people each year. In terms of methods and procedures, the research is both quantitative and qualitative, involving the collection, classification, and analysis of materials already used in traffic education by the Federal Highway Police, as well as the collection and analysis of internal data and the application of a questionnaire with experts in the field. The results include the categorization of previously used materials, evaluation of their acceptance, ease of use, and level of awareness generated, along with additional suggestions and identification of challenges and deficiencies in the area. Based on these results, a technical/technological product was developed: a portal that provides educational materials, including audiovisual resources, educational games, and printed materials, among others, for use in early childhood traffic education